Nuclear radiation shielding performance of borosilicate glasses: Numerical simulations and theoretical analyses. (March 2023) - Kilicoglu, O.; Akman, F.; Ogul, H.; Agar, O.; Kara, U.
Abstract: The photon shielding performances of five different borosilicate-based glasses were investigated in this study using the FLUKA, GEANT4 and MATLAB codes, as well as the XCOM program, at photon energies ranging from 0.03 to 15 MeV. In this context, dependencies of the photon attenuation features with the variation of the photon energy and the chemical compositions have been carefully evaluated with Monte Carlo simulation and theoretical evaluation tools. The mass attenuation coefficient values and effective atomic numbers obtained for BaO-doped G5 glasses are found to be higher than those derived for G1-G4 samples. In other words, the Zeff results showed that high Z-elements such as Ba in a suitable amount should be inserted into the glass composition in order to improve the photon attenuation capability of the borosilicate glasses. The HVLs, TVLs, and MFPs of the studied borosilicate glasses are determined further, and the gamma shielding characteristics of the analyzed samples are found to be associated to the density of the glass, implying that high-density glass can be used for high-level attenuation performance. The exposure buildup factor (EBF) values have been further estimated via the G-P fitting approach. The results of such investigations, according to the work given, may be valuable in designing and fabricating new borosilicate-based glasses, which can then shield against potential radiation damage to environmental health. Highlights: The photon shielding performances of five different borosilicate-based glasses. MAC, HVL, TVL, MFP, Zeff and EBF were determined for different borosilicate glasses. The MACs of various borosilicate glasses were estimated using simulation codes. Finding shows which sample has better photon attenuation performance.